Czech Republic : 2017 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Czech Republic. (IMF Staff Country Reports; Country Report, 2017)
This 2017 Article IV Consultation highlights the strong Czech economy. It grew by 2.4 percent in 2016, and unemployment is now the lowest in the European Union. Headline inflation is at the target, and external deflation pressure has faded. In addition, nominal incomes are growing solidly. Given momentum in the economy, real GDP growth is projected to increase to 3 percent in 2017, largely driven by domestic demand. Strong economic growth and better revenue collection mean a surplus of 0.4 percent of GDP is expected for 2017; current policies and improved tax collection would imply continued small surpluses from 2018.